Effect of Cleaning Methods on Trash Contents and Fibre Quality for Seed Cotton - Mishra, Pramod Kumar; Singh, Manjeet; Dixit, Anoop; Patel, Bharat; Gautam, Anand; Pandey, S. K.; Sharma, Karun (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out at Department of Farm Machinery and Power Engineering, Punjab Agricultural University, Ludhiana, India during May to December, 2017 to evaluate the effect of mechanical cleaning methods on mechanically harvested cotton. The treatments consisted of three cotton cleaning methods viz. Boll Crusher cum Seed-Cotton Extractor, Pre-cleaner and On-board cleaner (field cleaner). The comparative performance of these methods was evaluated in terms of cotton fibre quality parameters viz. span length, uniformity ratio, elongation (%), micronaire (%), fibre strength (g tex-1) and reflectance of cotton lint etc. The minimum trash content (seed cotton basis) was observed for boll crusher+pre-cleaner (5.17%) and maximum for on-board cleaner (21.4 %). The 2.5% span length for the manual was observed maximum (26.04 mm) and the minimum for boll crusher+pre-cleaner (23.83 mm). The uniformity ratio observed was minimum for manual (45.99) and maximum for boll crusher+pre-cleaner (47.29). The micronaire for the manual was observed as a minimum (3.97%) and maximum for boll crusher+pre-cleaner (3.57%). The fibre strength for manual (20.50 g tex-1) was maximum whereas it was minimum for boll crusher+pre-cleaner (19.36 g tex-1). The reflectance for manual (0.87) was observed as minimum and maximum for boll crusher+pre-cleaner (0.81). Based upon the fiber quality parameters of harvested cotton cleaned by boll crusher machine was of superior quality but it was inferior in quality for the boll crusher+pre-cleaner machine.